Optimized soil inversion in the headlands with a novel section‐controlled mouldboard ploughing system. (8th January 2020) - Nielsen, Søren Kirkegaard; Carstensen, Hans Christian; Munkholm, Lars J.; Nørremark, Michael; Rasmussen, Jesper; Bertl, Johanna; Labouriau, Rodrigo; Green, Ole
Abstract: In inversion tillage systems, the mouldboard plough is fundamental for producing a desirable seedbed. The desired ploughing quality is achieved when the plough layer is inverted homogeneously. This is, however, difficult to obtain in the main‐headland intersection zone where the plough is lowered and elevated, as ploughed and unploughed triangles are formed. This results in zones where the soil is inverted twice, which may result in poor residue and weed incorporation and a poor seedbed quality. The design of the three‐point linkage‐attached mouldboard plough has not changed since the 1950s, but the number of furrows has increased, which has increased the size of the aforementioned triangles. A novel ploughing system was introduced to meet these headland challenges, where each plough section can be lowered and elevated independently. The aim of this study was to evaluate the effects of using a section‐controlled mouldboard plough. Two similarly designed, randomized, field plot experiments were conducted on two different soil types (sandy loam and loamy sand) on a stubble field and grass field. The study showed that the section‐controlled plough reduced the main‐headland overlap area by 98%. The results of a range of soil physical properties measurements and seedbed quality analyses showed that the section‐controlled plough created a homogeneous loosened seedbed quality, improving the incorporation of crop residues and leaving fewer residues on the soil surface. Furthermore, the section‐controlled plough showed additional benefits, for example wedge operations and visual line marking.